Acrylate composite material, preparation method thereof and application of acrylate composite material in preparation of release film
By combining alginate-grafted acrylate-containing substance with cations of oxalate in the optical release film, acrylate composite material with a three-dimensional network structure is solved, and a high-performance antistatic film is achieved.
Patent Information
- Application Number
- CN202411987562.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing optical release film has low curing efficiency and poor antistatic stability during curing at high temperatures, which cannot achieve long-term protection, resulting in failure or contamination of the release film and adhesive layer, affecting product performance and application.
Alginic acid or sodium alginate is used as the core and is wrapped in the outer acrylate-containing substance. The acrylate-containing substance grafted through alginate is combined with the cation of the oxalate to form an acrylate composite material with a "point-core-outer" three-dimensional network structure.
It achieves a long-term anti-static effect, maintains the stability of the release film performance, and has excellent conductivity and high light transmittance, improving the durability and application performance of the product.
Smart Images

Figure CN119661780A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparing acrylate composite materials, in particular to an acrylate composite material and a preparation method thereof and application thereof in preparing a release film. Background Art
[0002] As the direct interface of human-computer interaction, touch transparent optical films and materials that make up touch flat panel displays have been widely used in various electronic products, smart cars, medical equipment and other fields. Optical release film is the most commonly used main substrate for touch transparent optical films, and its performance determines the quality of touch transparent optical films.
[0003] The optical release film contains acrylic silicone oil which is cured at high temperature. Currently, this curing method has some disadvantages, including low curing efficiency, poor antistatic stability, and inability to achieve long-term protection. It will lead to problems such as failure to peel off the release film and the adhesive layer or contamination, affecting product performance and application points. Therefore, this greatly limits the development of optical release films towards flexibility, lightweight, and electronicization. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an acrylate composite material, a preparation method thereof and an application thereof in preparing a release film.
[0005] The first object of the present invention is to provide an acrylate composite material, comprising an alginate or sodium alginate core, and an outer layer wrapped around the surface of the core, wherein the outer layer comprises an acrylate-containing substance grafted with alginate.
[0006] In some embodiments of the present invention, the molecular weight of the alginic acid or sodium alginate is 8000 to 74000;
[0007] The acrylate-containing substance includes one or more of vinyl acetate-acrylate, hydroxymethylethylene acrylate, hydroxyethyl methylacrylate, hydroxymethyl methylacrylate, hydroxyethyl acrylate, acrylamide-acrylate, and trimethylolpropane triacrylate.
[0008] The second object of the present invention is to provide a method for preparing the acrylic ester composite material, comprising the following steps:
[0009] ① Mix alginic acid or sodium alginate with an acid solution, and dehydrate it under acidic conditions to obtain modified alginate;
[0010] ② The modified alginate and oxalate obtained in step ① are mixed in an organic solvent to obtain a suspension, and then an acrylate-containing substance and N,N-dicyclohexylcarbodiimide are added, and the mixture is stirred and heated to react to achieve external grafting, thereby obtaining the acrylate composite material.
[0011] In some embodiments of the present invention, in step ①, the conditions of the dehydration reaction are: reaction temperature is ≤2°C, and reaction time is 3 to 6 hours;
[0012] The acid in the acid solution is selected from one or more of acetic acid, formic acid, and oxalic acid;
[0013] The concentration of the alginic acid or sodium alginate is 6 to 36 wt %;
[0014] The concentration of the acid solution is 0.45-1.2 wt %.
[0015] In some embodiments of the present invention, in step ②, the oxalate is selected from one or more of titanium oxalate, copper, magnesium, calcium, and silver;
[0016] The organic solvent is selected from one or more of toluene, xylene and pyrrolidone;
[0017] The weight proportions of the raw materials in the reaction are: 100 weight proportions of modified alginate, 10 to 18 weight proportions of oxalate, 500 to 2000 weight proportions of organic solvent, 5 to 45 weight proportions of acrylate-containing substance, and 1 to 4 weight proportions of N,N-dicyclohexylcarbodiimide;
[0018] The temperature of the heating reaction is 40-70° C., and the reaction time is 2-4 hours.
[0019] The third object of the present invention is to provide a durable antistatic composite coating, comprising a composite coating A and a composite coating B, wherein the composite coating A is composed of the following raw materials, in parts by mass: 25 to 65 parts by mass of the acrylate composite material according to claim 1 or 2, 8 to 15 parts by mass of polyether acrylate, 2 to 6 parts by mass of polyaniline, 8 to 15 parts by mass of acrylated polysiloxane, 0.2 to 0.8 parts by mass of an initiator, 1 to 1.8 parts by mass of hexamethylene diisocyanate, and 165 to 340 parts by mass of a solvent;
[0020] The composite coating B is composed of the following raw materials, in parts by mass: 10 to 30 parts by mass of the acrylate composite material according to claim 1 or 2, 20 to 45 parts by mass of polyurethane acrylate, 8 to 15 parts by mass of polyether acrylate, 2 to 6 parts by mass of polyaniline, 2 to 8 parts by mass of acrylated polysiloxane, 0.2 to 0.8 parts by mass of initiator, 1 to 1.8 parts by mass of hexamethylene diisocyanate, and 165 to 340 parts by mass of solvent.
[0021] In some embodiments of the present invention, the initiator is 2-hydroxy-2-methyl-phenylacetone;
[0022] The content of the acrylate composite material in the composite coating A is ≥ the content of the acrylate composite material in the composite coating B.
[0023] A fourth object of the present invention is to provide a release film, comprising a base film layer, an alternating layer and a second composite coating layer B arranged in sequence;
[0024] The alternating layer is formed by alternately coating the first composite coating layer B and the first composite coating layer A;
[0025] The first composite coating B layer includes the composite coating B;
[0026] The first composite coating A layer includes the composite coating A;
[0027] The second composite coating B layer includes the composite coating B;
[0028] The alternating layer contacts the base film layer and has at least one alternating layer perpendicular to the horizontal plane of the layer.
[0029] Furthermore, the composite coating A layer is partially on the surface of the first composite coating B layer.
[0030] In some embodiments of the present invention, the thickness of the base film layer is 45 to 225 μm;
[0031] The base film layer includes one or more of polybutylene terephthalate, polyethylene terephthalate, and polyethylene glycol-polybutylene terephthalate;
[0032] The first composite coating layer B and the first composite coating layer A are in staggered contact, and the first composite coating layer B and the first composite coating layer A are in direct contact with the base film layer;
[0033] The thickness of the alternating layer is 10 to 35 μm;
[0034] The thickness of the second composite coating layer B is 5 to 30 μm.
[0035] A fifth object of the present invention is to provide a method for preparing a release film, comprising the following steps:
[0036] (1) spraying polybutylene terephthalate uniformly on a carrier and rolling it to 45 to 225 μm to obtain a base film layer;
[0037] (2) immersing the base film layer in an organic solvent, coating the composite coating A on the base film layer, ultrasonically treating the composite coating A to corrugate the composite coating A to form a first composite coating A layer, coating the composite coating B on the surface of the first composite coating A layer, and drying to form an alternating layer;
[0038] (3) The composite coating B is then coated on the surface of the alternating layer, dried and stabilized, and then irradiated with ultraviolet light to obtain the release film.
[0039] In some embodiments of the present invention, in step (2), the organic solvent includes isopropanol and / or glycerol.
[0040] In some embodiments of the present invention, in step (2), the drying temperature is 70 to 105° C. and the drying time is 15 to 60 minutes.
[0041] In some embodiments of the present invention, in step (3), the wavelength of the ultraviolet light is 250 to 355 nm, and the irradiation time is 5 to 60 s.
[0042] In the present invention, high-frequency vibration is generated under ultrasonic treatment, and the coated composite coating A vibrates along with the vibration wave. The vibration wave generates compression and sparse areas for the composite coating A along with wave diffusion. The compression area is the peak, and the sparse area is the trough. The peak / trough spacing is 0.015 to 48 mm, and the composite coating A is corrugated.
[0043] The above technical solution of the present invention has the following advantages compared with the prior art:
[0044] The present invention uses alginate grafted acrylate-containing substances, uses alginate to connect external curable acrylate-containing substances as the outer layer, uses small molecule alginate or sodium alginate as the inner core, and uses the stable inner core to wrap cations of oxalate, and the cations serve as ion sites to form an acrylate composite material with a "site-inner core-outer layer" three-dimensional network structure. The cations have the function of continuously protecting the cations of oxalate from being destroyed, thereby achieving a long-term antistatic effect. The prepared durable antistatic composite coating can maintain the stability of the release film performance, and is an antistatic film with excellent conductive properties and high light transmittance.
[0045] By utilizing the high content of acrylic ester composite materials in the composite coating A, the first composite coating A layer is prepared and preferentially extruded and scraped on the base film layer to form a highly durable and antistatic first composite coating A layer, which serves as the "first coating layer" of the base film layer; after the first composite coating A layer is corrugated, the prepared first composite coating B layer is extruded and scraped on the base film layer and the first composite coating A layer to serve as the "second coating layer" of the base film layer, the first composite coating A layer and the first composite coating B layer form an alternating layer, and then the peaks of the first composite coating A layer are extruded to form a partial obtuse angle area, the contact area between the first composite coating A layer and the first composite coating B layer is increased, and the combination is more complete, thereby further improving the antistatic effect of the film, and the long-term protection ability is improved, and the coated alternating layer has good adhesion, structural stability, stable release effect and excellent transparency. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0047] Figure 1 Shown is a schematic diagram of the release film structure of Example 1 of the present invention. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0049] Example 1
[0050] The present invention provides a method for preparing an acrylate composite material and a release film, which are specifically as follows:
[0051] 1. Preparation method of acrylate composite material:
[0052] ① 8.4 wt% sodium alginate (small molecular weight of 65,000) was mixed with an aqueous solution containing 0.48 wt% oxalic acid, dehydrated in acid at -2°C for 5 hours, and then washed and dried with a 45 wt% ethanol aqueous solution to obtain modified alginate.
[0053] ② Mix 100 parts by weight of the modified alginate obtained in step ①, 10 parts by weight of calcium oxalate, and 900 parts by weight of solvent xylene in a reactor to obtain a suspension, then add 7.5 parts by weight of hydroxyethyl hydroxymethylacrylate and 1.8 parts by weight of N,N-dicyclohexylcarbodiimide, stir evenly, and place in an oven at 55°C to react for 2 hours for external grafting to obtain an acrylate composite material (with a long chain core).
[0054] 2. A durable antistatic composite coating, comprising composite coating A and composite coating B, wherein the durable antistatic composite coating comprises the above-mentioned acrylate composite material.
[0055] ① Preparation method of composite coating A: 30 parts by weight of acrylate composite material, 12 parts by weight of polyether acrylate, 3 parts by weight of polyaniline, 10 parts by weight of acrylated polysiloxane, 0.4 parts by weight of initiator 2-hydroxy-2-methyl-phenylacetone, and 260 parts by weight of solvent ethyl acetate are mixed and stirred evenly, and then 1.2 parts by weight of hexamethylene diisocyanate are added and stirred evenly to obtain composite coating A;
[0056] ② Preparation method of composite coating B: 10 parts by mass of acrylate composite material, 30 parts by mass of polyurethane acrylate, 8 parts by mass of polyether acrylate, 2 parts by mass of polyaniline, 5 parts by mass of acrylated polysiloxane, 0.4 parts by mass of initiator 2-hydroxy-2-methyl-phenylacetone, and 280 parts by mass of solvent ethyl acetate are mixed and stirred evenly, and then 1.2 parts by mass of hexamethylene diisocyanate are added to obtain composite coating B.
[0057] 3. Application: A release film, which is prepared as follows:
[0058] ① Evenly spray polybutylene terephthalate on a horizontal glass plate, remove it, and roll it to 100 μm to obtain the base film layer;
[0059] ② After the base film layer is soaked in propylene glycol for 4 days, the composite coating A is extruded and scraped onto the base film layer, and an ultrasonic treatment with a frequency of 65KHz is performed for 25 seconds. After that, the composite coating A coating is corrugated to form a first composite coating A layer with a peak spacing of 0.025mm (such as Figure 1 As shown), a composite coating B is extruded and scraped on the surface of the composite coating A layer, and the crests are squeezed after rolling, and the crests of the first composite coating A layer form an obtuse angle area, thereby increasing the contact area with the second composite coating B layer; the first composite coating B layer is dried at 50° C., and finally, an alternating layer with a thickness of 34 μm and an alternating first composite coating B layer and a composite coating A layer is obtained;
[0060] ③ Then apply the composite coating B on the alternating layer to obtain a second composite coating B layer with a thickness of 25 μm.
[0061] The first composite coating layer A is in contact with the base film layer, the first composite coating layer B and the second composite coating layer B. The coating is dried in a blast oven at 85° C. for 20 minutes and then irradiated with ultraviolet light in the wavelength range of 250 to 355 nm for 15 seconds to obtain a release film.
[0062] Example 2
[0063] The release film of this embodiment is prepared according to the preparation method of the above embodiment 1, with the only difference being:
[0064] A durable antistatic composite coating comprises a composite coating A and a composite coating B, wherein the durable antistatic composite coating comprises the acrylic ester composite material of the above-mentioned embodiment 1:
[0065] ① Preparation method of composite coating A: 35 parts by weight of acrylate composite material, 10 parts by weight of polyether acrylate, 3 parts by weight of polyaniline, 8 parts by weight of acrylated polysiloxane, 0.4 parts by weight of initiator 2-hydroxy-2-methyl-phenylacetone, and 260 parts by weight of solvent ethyl acetate are stirred evenly, and then 1.2 parts by weight of hexamethylene diisocyanate are added and stirred evenly to obtain composite coating A;
[0066] ② Preparation method of composite coating B: Mix 10 parts by mass of acrylate composite material, 35 parts by mass of polyurethane acrylate, 8 parts by mass of polyether acrylate, 2 parts by mass of polyaniline, 5 parts by mass of acrylated polysiloxane, 0.4 parts by mass of initiator 2-hydroxy-2-methyl-phenylacetone, and 280 parts by mass of solvent ethyl acetate, then add 1.2 parts by mass of hexamethylene diisocyanate and mix well to obtain composite coating B.
[0067] Example 3
[0068] The release film of this embodiment is prepared according to the preparation method of the above embodiment 1, with the only difference being:
[0069] A durable antistatic composite coating comprises a composite coating A and a composite coating B, wherein the durable antistatic composite coating comprises the acrylic ester composite material of the above-mentioned embodiment 1:
[0070] ① Preparation method of composite coating A: 45 parts by weight of acrylate composite material, 5 parts by weight of polyether acrylate, 3 parts by weight of polyaniline, 5 parts by weight of acrylated polysiloxane, 0.4 parts by weight of initiator 2-hydroxy-2-methyl-phenylacetone, and 260 parts by weight of solvent ethyl acetate are uniformly stirred in proportion, and then 1.2 parts by weight of hexamethylene diisocyanate are added to obtain the composite coating A;
[0071] ② Preparation method of composite coating B: 10 parts by mass of acrylate composite material, 40 parts by mass of polyurethane acrylate, 8 parts by mass of polyether acrylate, 2 parts by mass of polyaniline, 5 parts by mass of acrylated polysiloxane, 0.4 parts by mass of initiator 2-hydroxy-2-methyl-phenylacetone, and 280 parts by mass of solvent ethyl acetate are mixed and stirred evenly, and then 1.2 parts by mass of hexamethylene diisocyanate are added and mixed and stirred evenly to obtain the composite coating B.
[0072] Example 4
[0073] The release film of this embodiment is prepared according to the preparation method of the above embodiment 1, with the only difference being:
[0074] A release film, the release film is prepared as follows:
[0075] ① Spray polybutylene terephthalate uniformly on a horizontal glass plate, remove it, and roll it to 76 μm to obtain the base film layer;
[0076] ② After the base film layer is soaked in propylene glycol for 4 days, the composite coating A is extruded and scraped on the base film layer, and an ultrasonic treatment is performed at a frequency of 65KHz for 30 seconds. Then, the composite coating A coating is corrugated to form a first composite coating A layer with a wave peak spacing of 0.029mm. The composite coating B is extruded and scraped on the surface of the composite coating A layer. After rolling, the wave peaks are squeezed, and the wave peaks of the first composite coating A layer form an obtuse angle area, thereby increasing the contact area with the second composite coating B layer; the first composite coating B layer is dried at 50°C, and finally an interactive layer with a thickness of 22μm and an alternating first composite coating B layer and a composite coating A layer is obtained;
[0077] ③ The composite coating B is then coated on the alternating layer to obtain a second composite coating B layer with a thickness of 11 μm.
[0078] The first composite coating layer A is in contact with the base film layer, the first composite coating layer B and the second composite coating layer B. The coating is dried in a blast oven at 85° C. for 20 minutes and then irradiated with ultraviolet light in the wavelength range of 250 to 355 nm for 15 seconds to obtain a release film.
[0079] Example 5
[0080] The release film of this embodiment is prepared according to the preparation method of the above embodiment 1, with the only difference being:
[0081] 3. A release film, the release film is prepared as follows:
[0082] ① Spray polybutylene terephthalate evenly on a horizontal glass plate, remove it, and roll it to 75 μm to obtain the base film layer;
[0083] ② After the base film layer is soaked in glycerol for 4 days, the composite coating A is extruded and scraped on the base film layer, and an ultrasonic treatment is performed at a frequency of 65KHz for 28 seconds. After that, the composite coating A coating is corrugated to form a first composite coating A layer with a wave crest spacing of 0.023mm. The composite coating B is extruded and scraped on the surface of the composite coating A layer. After rolling, the crests are squeezed, and the crests of the first composite coating A layer form an obtuse angle area, thereby increasing the contact area with the second composite coating B layer; the first composite coating B layer is dried at 50°C, and finally an alternating layer with a thickness of 20μm and an alternating first composite coating B layer and a composite coating A layer is obtained;
[0084] ③ Then apply the composite coating B on the alternating layer to obtain a second composite coating B layer with a thickness of 12 μm.
[0085] The first composite coating layer A is in contact with the base film layer, the first composite coating layer B and the second composite coating layer B. The coating is dried in a blast oven at 85° C. for 20 minutes and then irradiated with ultraviolet light in the wavelength range of 250 to 355 nm for 18 seconds to obtain a release film.
[0086] Example 6
[0087] This embodiment provides a method for preparing an acrylate composite material and a release film, which is specifically as follows:
[0088] 1. A method for preparing an acrylic composite material;
[0089] ① 8.4 wt% sodium alginate (small molecular weight of 22,000) was mixed with 0.48 wt% oxalic acid aqueous solution, dehydrated in acid at 0°C for 4 hours, and then washed and dried with 45 wt% ethanol aqueous solution to obtain modified alginate.
[0090] ② Mix 100 parts by mass of the modified sodium alginate obtained in step ①, 15 parts by mass of magnesium oxalate, and 1400 parts by mass of solvent toluene in a reactor to obtain a suspension, then add 20 parts by mass of trimethylolpropane triacrylate and 3.0 parts by mass of N,N-dicyclohexylcarbodiimide, stir evenly, place in an oven at 55°C to react for 4 hours, perform external grafting, and obtain an acrylate composite material (with a long chain core).
[0091] 2. A durable antistatic composite coating, comprising composite coating A and composite coating B, wherein the durable antistatic composite coating comprises the above-mentioned acrylate composite material.
[0092] ① Preparation method of composite coating A: 50 parts by weight of acrylate composite material, 15 parts by weight of polyether acrylate, 6 parts by weight of polyaniline, 12 parts by weight of acrylated polysiloxane, 0.8 parts by weight of initiator 2-hydroxy-2-methyl-phenylacetone, and 320 parts by weight of solvent ethyl acetate are mixed and stirred evenly, and then 1.5 parts by weight of hexamethylene diisocyanate are added and stirred evenly to obtain the composite coating A;
[0093] ② Preparation method of composite coating B: 30 parts by mass of acrylate composite material, 20 parts by mass of polyurethane acrylate, 15 parts by mass of polyether acrylate, 5 parts by mass of polyaniline, 12 parts by mass of acrylated polysiloxane, 0.8 parts by mass of initiator 2-hydroxy-2-methyl-phenylacetone, and 300 parts by mass of solvent ethyl acetate are mixed and stirred evenly, and then 1.5 parts by mass of hexamethylene diisocyanate are added to obtain the composite coating B.
[0094] 3. Application: A release film, which is prepared as follows:
[0095] ① Spray polyethylene glycol-polybutylene terephthalate uniformly on a horizontal glass plate, remove it, and roll it to 76 μm to obtain the base film layer;
[0096] ② After the base film layer is soaked in propylene glycol for 4 days, the composite coating A is extruded and scraped on the base film layer, and an ultrasonic treatment is performed at a frequency of 65KHz for 45 seconds. Then, the composite coating A coating is corrugated to form a first composite coating A layer with a wave peak spacing of 0.034mm. The composite coating B is extruded and scraped on the surface of the composite coating A layer. After rolling, the wave peaks are squeezed, and the wave peaks of the first composite coating A layer form an obtuse angle area, thereby increasing the contact area with the second composite coating B layer; the first composite coating B layer is dried at 55°C, and finally an interactive layer with a thickness of 15μm and an alternating first composite coating B layer and a composite coating A layer is obtained;
[0097] ③ The composite coating B is then coated on the alternating layer to obtain a second composite coating B layer with a thickness of 14 μm.
[0098] The first composite coating layer A is in contact with the base film layer, the first composite coating layer B and the second composite coating layer B. The coating is dried in a blast oven at 85° C. for 15 minutes and then irradiated with ultraviolet light in the wavelength range of 250 to 355 nm for 18 seconds to obtain a release film.
[0099] Example 7
[0100] The release film provided in this embodiment is prepared according to the preparation method of the above embodiment 6, with the only difference being:
[0101] A durable antistatic composite coating comprises a composite coating A and a composite coating B, wherein the durable antistatic composite coating comprises the acrylic ester composite material of the above-mentioned embodiment 6:
[0102] ① Preparation method of composite coating A: 55 parts by weight of acrylate composite material, 10 parts by weight of polyether acrylate, 6.5 parts by weight of polyaniline, 12 parts by weight of acrylated polysiloxane, 0.8 parts by weight of initiator 2-hydroxy-2-methyl-phenylacetone, and 320 parts by weight of solvent ethyl acetate are uniformly stirred in proportion, and then 1.5 parts by weight of hexamethylene diisocyanate are added and stirred to obtain the composite coating A;
[0103] ② Preparation method of composite coating B: 30 parts by mass of acrylate composite material, 25 parts by mass of polyurethane acrylate, 8 parts by mass of polyether acrylate, 5.5 parts by mass of polyaniline, 12 parts by mass of acrylated polysiloxane, 0.8 parts by mass of initiator 2-hydroxy-2-methyl-phenylacetone, and 320 parts by mass of solvent ethyl acetate are mixed and stirred evenly, and then 1.5 parts by mass of hexamethylene diisocyanate are added to obtain the composite coating B.
[0104] Example 8
[0105] The release film of this embodiment is prepared according to the preparation method of the above embodiment 6, with the only difference being:
[0106] A durable antistatic composite coating comprises a composite coating A and a composite coating B, wherein the durable antistatic composite coating comprises the acrylic ester composite material of the above-mentioned embodiment 6:
[0107] ① Preparation method of composite coating A: 55 parts by weight of acrylate composite material, 10 parts by weight of polyether acrylate, 6.5 parts by weight of polyaniline, 12 parts by weight of acrylated polysiloxane, 0.8 parts by weight of initiator 2-hydroxy-2-methyl-phenylacetone, and 320 parts by weight of solvent ethyl acetate are mixed and stirred uniformly, and then 1.5 parts by weight of hexamethylene diisocyanate are added to obtain the composite coating A;
[0108] ② Preparation method of composite coating B: 30 parts by mass of acrylate composite material, 25 parts by mass of polyurethane acrylate, 10 parts by mass of polyether acrylate, 5.5 parts by mass of polyaniline, 12 parts by mass of acrylated polysiloxane, 0.8 parts by mass of initiator 2-hydroxy-2-methyl-phenylacetone, and 1900 parts by mass of solvent ethyl acetate are mixed and stirred evenly, and then 1.5 parts by mass of hexamethylene diisocyanate are added to obtain the composite coating B.
[0109] Example 9
[0110] The release film of this embodiment is prepared according to the preparation method of the above embodiment 6, with the only difference being:
[0111] A release film, the release film is prepared as follows:
[0112] ① Spray polyethylene glycol-polybutylene terephthalate uniformly on a horizontal glass plate, remove it, and roll it to 72 μm to obtain the base film layer;
[0113] ② After the base film layer is soaked in propylene glycol for 6 days, the composite coating A is extruded and scraped on the base film layer, and an ultrasonic treatment is performed at a frequency of 55KHz for 15 seconds. Then, the composite coating A coating is corrugated to form a first composite coating A layer with a wave peak spacing of 0.017mm. The composite coating B is extruded and scraped on the surface of the composite coating A layer. After rolling, the wave peaks are squeezed, and the wave peaks of the first composite coating A layer form an obtuse angle area, thereby increasing the contact area with the second composite coating B layer; the first composite coating B layer is dried at 55°C, and finally an interactive layer with a thickness of 10μm and an alternating first composite coating B layer and a composite coating A layer is obtained;
[0114] ③ Then apply the composite coating B on the alternating layer to obtain a second composite coating B layer with a thickness of 5 μm.
[0115] The first composite coating layer A is in contact with the base film layer, the first composite coating layer B and the second composite coating layer B. The coating is dried in a blast oven at 85° C. for 15 minutes and then irradiated with ultraviolet light in the wavelength range of 250 to 355 nm for 18 seconds to obtain a release film.
[0116] Comparative Example 1
[0117] The difference between Comparative Example 1 and Example 1 is that hydroxyethyl hydroxymethylacrylate is directly used for preparation without adding sodium alginate, and the rest is the same as Example 1.
[0118] Comparative Example 2
[0119] The difference between Comparative Example 2 and Example 1 is that the composite coating A of a durable antistatic composite coating does not contain the acrylic composite material of Example 1, and the rest is the same as Example 1.
[0120] Comparative Example 3
[0121] The difference between Comparative Example 3 and Example 1 is that: the alternating layer does not contain the composite coating A, forming the first composite coating A layer, the alternating layer is entirely the first composite coating B layer, and the rest is the same as Example 1.
[0122] Comparative Example 4
[0123] The difference between Comparative Example 4 and Example 6 is that: the alternating layer does not contain the composite coating A, forming the first composite coating A layer, and the alternating layer is entirely the first composite coating B layer, and the rest is the same as Example 6.
[0124] Performance Testing
[0125] 1. Stability test:
[0126] The release films obtained in the above examples and comparative examples were placed in an oven at a temperature of 25±2°C, a relative humidity of 40% to 65%, and an air flow of 500 mL / h for 3 days and 21 days, respectively, and the following test was performed to compare the performance stability of the release films after being placed for 3 days and 21 days:
[0127] (1) Use a probe to measure the resistivity r of the release film, where square resistance R = r*thickness of release film / (length of release film*width of release film);
[0128] (2) Deformation: Spread the release film flat to see if there is any obvious deformation (such as stripes, waves or other shapes);
[0129] (3) Use an ultraviolet spectrophotometer to test the transmittance of the release film in the wavelength range of 300 to 800 nm, and use a blank glass slide as the test background, and calculate the transmittance at 520 nm and 550 nm. The higher the transmittance, the better the optical transparency;
[0130] (4) Rainbow pattern: Cut the release film and place it on a black flat table. Shine a light on the surface of the release film and observe the surface of the release film at 30°C to see if there are striped rainbow patterns.
[0131] (5) Haze: Cut the release film and measure the haze value of the release film using a haze meter.
[0132] The test results are shown in Table 1 and Table 2.
[0133] Table 1
[0134]
[0135]
[0136] Table 2
[0137]
[0138] As shown in Tables 1 and 2, compared with Examples 1 to 9, in Comparative Example 1, no sodium alginate was added, and the prepared acrylate composite material lacked small molecule alginate as the core, resulting in large changes in the square resistance R, transmittance, and haze of Comparative Example 1, and rainbow patterns could be distinguished, and the antistatic and transmittance stability were poor, indicating that the structural stability of the acrylate composite material was deteriorated, and the stability of the release film performance was greatly affected; in Comparative Example 2, no acrylate composite material was added, and the square resistance R was the largest and the change increased by 0.34×10 9 Ω / □ The light transmittance decreased by 2.3%, which is slightly greater than that of the embodiment, indicating that the antistatic effect is the worst without the addition of the acrylic composite material, and the stability of the release film performance is affected; the interactive layer of the release film of Examples 3 and 4 does not have the composite coating A, and the square resistance R shows an obvious trend of increase, light transmittance, deformation, and rainbow patterns are more likely to appear. In short, by using small molecule alginate as the core and cations as ion sites, an acrylic composite material with a three-dimensional network structure of "point-core-outer layer" is formed, which has a sustained antistatic effect; the first composite coating A layer and the first composite coating B layer form an interactive layer with improved long-term protection ability, which can maintain the stability of the release film performance. The obtained release film has a lasting antistatic effect, excellent transparency and a stable release effect.
[0139] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. An acrylic composite material, characterized in that: The invention comprises an alginate or sodium alginate inner core and an outer layer wrapped on the surface of the inner core, wherein the outer layer comprises an acrylate-containing substance grafted with alginate.
2. The acrylate composite material according to claim 1, characterized in that: The molecular weight of the alginic acid or sodium alginate is 8000 to 74000; The acrylate-containing substance includes one or more of vinyl acetate-acrylate, hydroxymethylethylene acrylate, hydroxyethyl methylacrylate, hydroxymethyl methylacrylate, hydroxyethyl acrylate, acrylamide-acrylate, and trimethylolpropane triacrylate.
3. The method for preparing the acrylate composite material according to claim 1 or 2, characterized in that: The following steps are involved: ① Mix alginic acid or sodium alginate with an acid solution, and dehydrate it under acidic conditions to obtain modified alginate; ② The modified alginate and oxalate obtained in step ① are mixed in an organic solvent to obtain a suspension, and then an acrylate-containing substance and N,N-dicyclohexylcarbodiimide are added, and the mixture is stirred and heated to react to achieve external grafting, thereby obtaining the acrylate composite material.
4. The preparation method according to claim 3, characterized in that: In step ①, the conditions of the dehydration reaction are: reaction temperature is ≤2°C, and reaction time is 3 to 6 hours; The acid in the acid solution is selected from one or more of acetic acid, formic acid, and oxalic acid; The concentration of the alginic acid or sodium alginate is 6 to 36 wt %; The concentration of the acid solution is 0.45-1.2 wt %.
5. The preparation method according to claim 3, characterized in that: In step ②, the oxalate is selected from one or more of titanium oxalate, copper, magnesium, calcium, and silver; The weight proportions of the raw materials in the reaction are: 100 weight proportions of modified alginate, 10 to 18 weight proportions of oxalate, 500 to 2000 weight proportions of organic solvent, 5 to 45 weight proportions of acrylate-containing substance, and 1 to 4 weight proportions of N,N-dicyclohexylcarbodiimide; The temperature of the heating reaction is 40-70° C., and the reaction time is 2-4 hours.
6. A durable antistatic composite coating, characterized in that: The invention comprises a composite coating A and a composite coating B, wherein the composite coating A is composed of the following raw materials, in parts by mass: 25 to 65 parts by mass of the acrylate composite material according to claim 1 or 2, 8 to 15 parts by mass of polyether acrylate, 2 to 6 parts by mass of polyaniline, 8 to 15 parts by mass of acrylated polysiloxane, 0.2 to 0.8 parts by mass of an initiator, 1 to 1.8 parts by mass of hexamethylene diisocyanate, and 165 to 340 parts by mass of a solvent; The composite coating B is composed of the following raw materials, in parts by mass: 10 to 30 parts by mass of the acrylate composite material according to claim 1 or 2, 20 to 45 parts by mass of polyurethane acrylate, 8 to 15 parts by mass of polyether acrylate, 2 to 6 parts by mass of polyaniline, 2 to 8 parts by mass of acrylated polysiloxane, 0.2 to 0.8 parts by mass of initiator, 1 to 1.8 parts by mass of hexamethylene diisocyanate, and 165 to 340 parts by mass of solvent.
7. The composite coating A and composite coating B of the durable antistatic composite coating according to claim 6, characterized in that: The initiator is 2-hydroxy-2-methyl-phenylacetone; The content of the acrylate composite material in the composite coating A is ≥ the content of the acrylate composite material in the composite coating B.
8. A release film, characterized in that: It includes a base film layer, an alternating layer and a second composite coating layer B which are arranged in sequence; The alternating layer is formed by alternately coating the first composite coating layer B and the first composite coating layer A; The first composite coating B layer comprises the composite coating B according to claim 6 or 7; The first composite coating A layer comprises the composite coating A according to claim 6 or 7; The second composite coating B layer comprises the composite coating B according to claim 6 or 7; The alternating layer contacts the base film layer and has at least one alternating layer perpendicular to the horizontal plane of the layer.
9. The release film according to claim 8, characterized in that: The thickness of the base film layer is 45 to 225 μm; The base film layer includes one or more of polybutylene terephthalate, polyethylene terephthalate, and polyethylene glycol-polybutylene terephthalate; The first composite coating layer B and the first composite coating layer A are in staggered contact, and the first composite coating layer B and the first composite coating layer A are in direct contact with the base film layer; The thickness of the alternating layer is 10 to 35 μm; The thickness of the second composite coating layer B is 5 to 30 μm.
10. The method for preparing the release film according to claim 9 or 10, characterized in that: The following steps are involved: ① Spray polybutylene terephthalate evenly on the carrier and roll it to 45-225 μm to obtain a base film layer; ② Soaking the base film layer in an organic solvent, applying the composite coating A on the base film layer, ultrasonically treating, corrugating the composite coating A to form a first composite coating A layer, applying the composite coating B on the surface of the first composite coating A layer, and drying to form an alternating layer; ③ The composite coating B is then coated on the surface of the alternating layer, dried and stabilized, and then irradiated with ultraviolet rays to obtain the release film.
Citation Information
Patent Citations
Release film and method for manufacturing the same
CN102666094A
High-brightness and high-haze light homogenizing film
CN112305648A
Novel water-based ultraviolet-curing wear-resistant coating as well as preparation method and use method thereof
CN112480805A
Pressure-sensitive adhesive sheet
JP2003105288A